Determinant of audit reporting lag: a case of Malaysia / Sarimah Yamin - Yamin, Sarimah (2015)
This objective of this study is to investigate the determinants of audit reporting lag that may impact the timeliness of annual reports. Specifically, the study examines the relationship between audit reporting lag and type of auditor, CEO duality, audit committee size, audit committee independence and audit committee meeting. This study also controls the possible effect of company size, profitability, leverage, growth and industry to the audit reporting lag. Based on 729 annual reports of companies listed in Bursa Malaysia, the study finds that 99 days are the average reporting lag for listed company in Malaysia on 2014. Consistent with prior finding the study finds negative significant relationship between audit reporting lag and type of auditor and audit committee size. In addition, the findings show that C EO duality is seemingly not significant factors influencing the audit reporting lag in Malaysia. Meanwhile, audit reporting lag has a positive relationship with audit committee independence and audit committee meeting. Apart from this, company big size and profitable company tend to have a shorter audit reporting lag. On the other hand, leverage and growth do not significantly effect the delay in financial reporting. This study concludes that the type of auditor, audit committee size, audit committee independence and audit committee meeting are important determinants of audit reporting lag.